(untitled) (Vietnam Journal of Community Medicine, 2025)
Background: Endometrial polyp is a frequent gynecological benign leison. It can lead to abnormal uterin bleeding, anemia, infertility, abortion, malignancy. Hyteroscopy has been applied at Nghe An Obstetrics and Pediatrics hospital since 2019 to investigate uterine pathologies. The aim of this study was to describe the clinical and subclinical charateristics of patients with endometrial polyps, analyse the results of treatment of endometrial polyps with hysteroscopic surgery. Methods: Cross section. Results: There were 112 patients included in the study. Mean age was 34,97 ± 7,65. The most common symptom was abnormal uterine bleeding (21,4%), most of the cases had no clinical sign (58,9%). There were 75,7% cases diagnosed by saline infused sonogram. The diameter of the polyps ranges mostly 10 – 20mm (50,9%). The main treatment method is using endocsopic instruments (95,5%), there was 1 case of uterin perforation (0,9%). Histopathological results: endometrial polyps 95,5%, uterine fibroids 3,6%, no maglignant case. The average length of hospical stay was 3 ± 0,5 days, most patients had menstrual cycle again after 1 month (83,3%). There was association between the treatment method and polyp size, with the value of p = 0,0001. Conclusion: Hysteroscopy is an effective and safe method to treat endometrial polyps